Computer tablet or telephone? A randomised controlled trial exploring two methods of collecting data from drug and alcohol outpatients. (August 2017) - Hobden, Breanne; Bryant, Jamie; Carey, Mariko; Sanson-Fisher, Rob; Oldmeadow, Christopher
Abstract: Objective: Both computerised and telephone surveys have potential advantages for research data collection. The current study aimed to determine the: (i) feasibility, (ii) acceptability, and (iii) cost per completed survey of computer tablet versus telephone data collection for clients attending an outpatient drug and alcohol treatment clinic. Design: Two-arm randomised controlled trial. Method: Clients attending a drug and alcohol outpatient clinic in New South Wales, Australia, were randomised to complete a baseline survey via computer tablet in the clinic or via telephone interview within two weeks of their appointment. All participants completed a three-month follow-up survey via telephone. Results: Consent and completion rates for the baseline survey were significantly higher in the computer tablet condition. The time taken to complete the computer tablet survey was lower (11 min) than the telephone condition (17 min). There were no differences in the proportion of consenters or completed follow-up surveys between the two conditions at the 3-month follow-up. Acceptability was high across both modes of data collection. The cost of the computer tablet condition was 67.52 greater per completed survey than the telephone condition. Conclusion: There is a trade-off between computer tablet and telephone data collection. While both data collection methods were acceptable to participants, the computer tablet condition resulted in higher consent and completion rates at baseline, therefore yielding greater external validity, and was quicker for participants to complete. Telephone data collection was however, more cost-effective. Researchers should carefully consider the mode of data collection that suits individual study needs. Highlights: The optimal method of data collection in drug and alcohol clinics is unknown. The feasibility of computer tablet versus telephone data collection is examined. The computer tablet yielded higher consent and completion rates at baseline. There were no differences between the two conditions at the 3-month follow-up. The computer tablet cost was 67.52 greater per completed survey than telephone.